Fish derived polyunsaturated fatty acids and their health effects: the influence of mercury - Nowicka, Grażyna (Studia Ecologiae et Bioethicae, 2005)
Fatty acids derived from fish and fish oils have a strong beneficial effect on cardiovascular health and neurodevelopment. Dietary omega 3 fatty acids prevent cardiovascular disease development by the influence on eicosanoid synthesis, cytokine and growth factors production, lipid and lipoprotein metabolism, endothelial relaxation. They have a strong antiarrhytmic action on the heart. Enhanced consumption of fish derived fatty acids is related to the low incidence of cardiovascular events and sudden cardiac deaths. High content of mercury in some fishes may attenuate the beneficial effects of omega 3 fatty acids on cardiovascular health and also on neurodevelopment of newborns and children